Increasing the Service Efficiency of Customs Employees through Motivational Factors (Zien Journal of Social Sciences and Humanities, 2025)
This article is dedicated to the significance of motivational factors in improving the performance of employees of the State Customs Service of the Republic of Uzbekistan. Customs authorities play an important role in society and the country's economy by ensuring the state's economic security and positively influencing development. Employee motivation, in turn, determines the level of work efficiency and directly impacts their enthusiasm, responsibility, and desire to achieve success. The article explores key factors for enhancing the motivation of customs service employees, including material and non-material incentives, social protection and guarantees, opportunities for professional development, and organizational support. Moreover, the article develops the most effective methods for improving the performance of customs service employees through the optimization of motivational factors. This study offers significant practical recommendations for increasing the efficiency of customs authorities and strengthening their role in public administration.